Getting Ready for Second Grade - Smith, Jodene (Summer Blast Ser., 2016)
Keep students sharp during the summer months with fun theme-based units including language arts, mathematics, and critical and creative thinking activities. Support parents with everyday learning ideas and a handbook about today's standards.